The role of commercial bank in financing small and medium enterprises: Evidence from Majmaa city during 2020- 2021 - Mohamed, Emad Suliman Sharif; Abdalla, Sumia Ibrahim Ahmed (Journal of Economic, Administrative and Legal Sciences, 2022)
This research aims to study the role of commercial banks in financing small and medium enterprises in the Kingdom of Saudi Arabia. The small and medium enterprises sector considered as an important sector in the national economy, due to its contribution to providing jobs, and an Increasing in Individual Income. The study assumes a statistically significant relationship between the financing of commercial banks and small and medium enterprises.In this research, the descriptive- analytical approach was used for obtaining the relevant primary data. In this regard, the researchers have designed a questionnaire to collect the necessary answers to study the variables of the study and test the study hypotheses. Moreover, the other approach that the researchers relied on is the deductive approach, where information deduced from original sources and references. The Important results we have achieved here, Small and medium enterprises Provides estimated percentage of employment, the financing provided does not comply with the client's requirements, and the conditions imposed by commercial banks on projects are intractable.The most important recommendations is, an Increasing the amount of financing provided to small and medium enterprises, Facilitating the conditions for granting loans to small and medium enterprises, and The state and official bodies must sponsor this type of project so that it can exercise its active role in the society.
Keywords: Financing; Small and medium enterprises; Employment